Coexistence of Riehl’s Melanosis, Lupus Erythematosus and Thyroiditis in a Patient - Lai K; Zheng X; Wei S; Zhou H; Zeng X; Liang G; Zhang Z; Zhang W (Dove Medical Press, 2022)
Kuan Lai,1 Xinyao Zheng,1 Shanshan Wei,2 Huifeng Zhou,1 Xuedan Zeng,1 Guixin Liang,1 Zhiwen Zhang,1 Wenjing Zhang3 1Department of Dermatology, Nanfang Hospital, Southern Medical University, Guangzhou, People's Republic of China; 2Department of Dermatology, Zhujiang Hospital, Southern Medical University, Guangzhou, People's Republic of China; 3Department of Dermatology, The First Affiliated Hospital of Jinan University, Guangzhou, People's Republic of ChinaCorrespondence: Wenjing Zhang, Department of Dermatology, The First Affiliated Hospital of Jinan University, No. 613, West Huangpu Avenue, Tianhe District, Guangzhou, 510630, People's Republic of China, Email WJ_Z0817@163.comIntroduction: Riehl's melanosis (RM) is an acquired hyperpigmentation disorder, presenting diffused and reticulate brownish-gray pigmentation, preferentially on the face and neck. RM overlaps with systemic lupus erythematosus (SLE) and Hashimoto's thyroiditis has never been reported.Case: We report a case of RM patient accompanied with SLE and Hashimoto's thyroiditis of primary hypothyroidism. Progressing, diffuse, symmetric, and reticular hyperpigmentation was seen on the face, neck, and upper limbs, manifesting as typical melanosis. Skin microscopy showed diffuse black-pepper-like changes and telangiectasias. The diagnosis of SLE and primary hypothyroidism were confirmed by follow-up investigations. The hyperpigmentation turned notably lighter after 14 months of treatment with prednisone, hydroxychloroquine, and L-thyroxine.Discussion: The exact pathogenesis of RM is unclear and exposure to coal tar dyes, ultraviolet, and fragrance fixatives in cosmetics are believed to be contributing factors, while some cases involve no triggers. It is not impossible that RM is a rare skin manifestation of SLE that has never been reported. The skin hyperpigmentation in this patient was not triggered by thyroid disease.Conclusion: RM could be a skin manifestation of autoimmunity. Coexistence of RM, lupus erythematosus and thyroiditis in the same patient is rare and has never been reported.Keywords: case report, melanosis, cutaneous lupus erythematosus, systemic lupus erythematosus, primary hypothyroidism